Pengaruh Pengetahuan Pajak, Pengetahuan Zakat dan Sikap Terhadap Kepatuhan Wajib Pajak Muslim - Muhammad Yusuf; Tubagus Ismail (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
The synergy of tax and zakat regulation contained in the law of Republic Indonesia number 38 of 1999 on zakat management and number 17 of 2000 on income tax, can be seen as step forward in the integration of tax and zakat. The Muslim taxpayers’ knowlegde about the existance of this synergy is important for cultivating obidient behaviour that can affect taxpayer’s attitude in implementing tax compliance by making zakat as a deduction of taxable income.This thesis disscusses the influences of tax knowledge, knowledge of zakat, and tax compliance attitude of muslim taxpayers. In this case, the author focuses on the direct and indirect influences between tax knowledge, knowledge of zakat, and tax compliance attitude of muslim taxpayers.This research was conducted on 178 respondents, which are KPP Pratama taxpayers of the City of Depok, by taking samples directly in the field, with the use of questionaires as a data collection tool. Structural Equation Modeling (SEM) was used for data analysis, using the SPLS 2.0 program.The results showed that there is a direct influence of tax knowledge, knowledge of zakat, and tax compliance attitude of muslim taxpayers. The results also indicated the indirect influence between tax knowledge, knowledge of zakat, and tax compliance attitude of muslim taxpayers.